Pengaruh Campuran Bioetanol – Pertamax 92 Terhadap Kinerja Motor Otto - Sugeng Hadi Susilo; Angga Muhammad Sabudin (Jurnal Energi dan Teknologi Manufaktur, 2018)
Problems in the process of burning fossil fuels still produce power and torque of the engine with large fuel oil needs. Various ways can be done to improve engine performance by using bioethanol as a mixture of pertamax without reducing engine power and torque, the use of fuel pertamax may reduce. The purpose of the study to determine effect of the use of bioethanol mixture with pertamax fuel to power and torque of gasoline engine, in addition to know the working temperature of radiator water and exhaust gas especially the injection system capacity of 150 cc. The study process uses experimental method which is devided into several steps: mixture bioetanol and pertamax 92 with volume comparison, vehicle power and torque test use chasis dynamometer, working temperatur of radiator water and exhaust gas test use sensor thermocouple K type. The results of the study indicate that in the Bp 30% mixture on 8000 rpm, the power is increased by 12.92 Hp with radiator water temperature of 52.96 °C at the exhaust gas of 126.85 °C. While the torque is increased by 13.47 Nm blend of Bp 30% at 6000 rpm with radiator water temperature of 52.51 °C at the exhaust gas of 136.15 °C. Based on the result mixture bioetanol and pertamax 92 with precentages 30% increased vehicle power and torque.